The Compliance of Governance on Family Data Protection Regulation - Ni Komang Sutrisni; Putu Angga Pratama Sukma; Embong , Rahimah; Haydarov , Khanlar (Lembaga Contrarius Indonesia, 2024)
Digital transformation has changed the way family data is managed and stored. The vulnerability of family data has become a serious concern due to the increase in data breach incidents. This research aims to analyze public compliance with family data protection regulations and the ideality of government governance regulations regarding family data protection regulations. This research uses normative legal research methods to analyze the comparison of family data privacy protection regulations between Indonesia and England. This research examines various legal guidelines and policies by applying legislative techniques and a conceptual approach. The legal system theory is used as an analytical framework to evaluate the effectiveness of regulations, law enforcement, and legal culture's influence on public compliance. Data was collected through a literature review of primary and secondary sources, including documents, archives, books, and scientific research findings. The research results show First, that family data protection regulations in England are first more standardized with a higher level of public compliance than in Indonesia. Secondly, Indonesia still faces challenges such as the weak bargaining position of data subjects, the absence of clear guidelines for data controllers, and the need for an independent oversight authority. This research recommends regulatory improvements, the establishment of competent authorities, and enhanced public education to strengthen Indonesia's personal data protection system, particularly family data.